Toward a Coalition in Support of the Awareness and Identity of New Academic Workers in Mexican Higher Education. Issue 3 (September 2015) - Ramos, Arturo; Lechuga, María Teresa; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> The neoliberal policies implemented since the 1980s in Mexico and the world have deteriorated conditions of academic work measures imposing labor flexibility and precariousness for most teachers in higher education. This New Academic Majority needs a political revival. The reorganization of this sector becomes an urgent task for academics and their unions.